Multiple effects of business plans on new ventures - Burke, Andrew; Fraser, Stuart; Green, Francis (Cranfield University School of Management, 2009)
We investigate the impact of writing a business plan prior to start-up on new venture performance. Our analysis makes new contributions by examining multiple effects of business plans. This approach allows the impacts of business plans to be disentangled from selection effects due to differences in the profile and business context of ventures that are more or less likely to write a business plan. We offer an empirical methodology and apply it to UK data where we find that business plans promote employment growth. This is found to be due to the impact of the plan and not selection effects.
Keywords: New Ventures; Business Plans; Switching regression modelling